The impact of personal attitudes on the growth ambitions of small business owners. Issue 4 (20th November 2017) - Braidford, Paul; Drummond, Ian; Stone, Ian
Abstract : Purpose: The purpose of this paper is to provide an empirical evidence in support of widespread calls for new approaches to understanding small business growth, by exploring the use of non-positivist methods (e.g. critical realism) to analyse how owners' innate dispositions shape growth in practice. Design/methodology/approach: In 2014, a telephone survey was used to inform two focus groups and 29 in-depth interviews with small business owners throughout England, covering attitudes towards growth, the use of particular strategies and perceived barriers. Discourse analysis was used to develop a multi-layered explanatory model incorporating key ideas from critical realism and the work of Bourdieu. Findings: Bourdieusian analysis reveals the existence of orientations among small business owners towards or against business growth. Such attitudes tend to impact upon their response to perceived barriers. Growth-inclined owners were willing to strategise for long-term benefit, in return for lower returns in the short term. Growth-resistant owners were more likely to view obstacles as absolute, stating that they cannot grow their firms as a result. Practical implications: Removing or reducing obstacles may not encourage growth if motivations and attitudes of owners do not change to embrace more growth-oriented positions. Banks' lending practices, for example, were seen by many as problematic, but growth-oriented owners were more willing to seek and use alternatives to raise funds for growth. Originality/value: The authors suggest that entrepreneurship researchers should look beyond positivist research to epistemologies that provide more multi-layered modes of explanation.